2002
DOI: 10.1086/345549
|View full text |Cite
|
Sign up to set email alerts
|

2MASS 1315−2649: A High Proper-Motion L Dwarf with Strong Hα Emission

Patrick B. Hall

Abstract: In a previous Letter, I reported that 2MASSI J1315309Ϫ264951 is an L dwarf with strong Ha emission. Two spectroscopic epochs appeared to show that the Ha was variable, decreasing from 121 to 25 Å EW, which I interpreted as a flare during the first observation. Gizis independently discovered this object, and his intermediate spectroscopic epoch shows Ha with 97 Å EW. A new fourth epoch of spectroscopy again shows a very large Ha EW (124 Å ), confirming this object to be a persistent, strong Ha emitter. Whether … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…These are heavily blended with airglow lines known for the UVES instrument (Hanuschik 2003). The EW for H α of 24.1 Å seems to imply that the brown dwarf is in a rather quiescent state since Hall (2002) found EW of 121 Å and of 25 Å half a year later. …”
Section: A2 Ad Leo Yz CMI Prox Cen and Lhs 292mentioning
confidence: 89%
“…These are heavily blended with airglow lines known for the UVES instrument (Hanuschik 2003). The EW for H α of 24.1 Å seems to imply that the brown dwarf is in a rather quiescent state since Hall (2002) found EW of 121 Å and of 25 Å half a year later. …”
Section: A2 Ad Leo Yz CMI Prox Cen and Lhs 292mentioning
confidence: 89%
“…Flares on brown dwarfs appear to be less frequent than on M dwarfs, but have been seen in both X-ray and radio (Berger et al 2001). Optical spectra have shown variable Hα emission in L dwarfs (Hall 2002;Liebert et al 2003;Reiners & Basri 2008) that may be the result of flares. LSST's new observations of such a large number of brown dwarfs over dozens of epochs will provide much-needed empirical determinations of flare rates.…”
Section: Variability Of Vlm Stars and Brown Dwarfsmentioning
confidence: 99%
“…The limited observations of 2M1022+58 suggest similarities between the two objects, as H emission in PC 0025 also varies by an order of magnitude. Hall (2002) suggested that the L3 dwarf 2MASSI J1315309À 264951 (hereafter 2M1315À26) shows similar strong, variable activity. It has been observed twice with an H EW of $120 8 [log (F H /F bol ) ¼ À4], and two other epochs of spectroscopy show H EWs of 97 and 25 8.…”
Section: Strong H Emission From the L1 Dwarf 2mass J10224821+5825453mentioning
confidence: 99%